Cryo-X-ray tomography (Cryo-XT) of viral factories in cells infected with Vaccinia virus - Moreno-Serrano, José Antonio (2018)
VV (Vaccinia virus) is one of the most complex viruses, with a size greater than 300 nm and more than 100 structural proteins. Its assembly involves sequential interactions and important rearrangements of its structural components. The BSC40 cells were infected and then selected by light fluorescence microscopy and subsequently imaged under the X-ray microscope under cryogenic conditions. Tomographic tilt series of X-ray images were used to produce three-dimensional reconstructions showing different cellular organelles (nuclei, mitochondria, RE), together with two other types of viral particles related to different stages of immature vaccinia (IV) maturation and (MV) mature particles; tests with witaferin showed links with actin, which prevents polymerization and elongation of the filaments; causing poorly packaged or aberrant virions, which inhibits the progression of the viral infection. The findings demonstrate that X-ray cryo-tomography is a powerful tool to collect three-dimensional structural information from frozen whole cells, unfixed and without spots with sufficient resolution to detect different virus particles that exhibit different levels of maturation.